Variation in gynogenic potential for haploid induction in Indian shortday onions - Anandhan, Sivalingam; Chavan, Ashwini A.; Gopal, Jai; Mote, Sanjay R.; Shelke, Poonam V.; Lawande, Kisan E. (The Indian Journal of Genetics and Plant Breeding, 2016)
Gynogenic haploid induction was tried in 14 Indian shortday onion varieties. Variation in gynogenic potential was observed (0.9 to 4.5 per cent) between genotypes. The highest frequency of gynogenic plants was in Bhima Shubhra (4.5 %) and the lowest in Bhima Shweta (0.9 %). Accumulation of mutant alleles likely contributed to the low gynogenic frequency. Time to embryo sprouting varied between 40 to 98 days after inoculation. Highest range in time of sprouting was observed in Bhima Shubhra, from 51 to 98 days. Non-haploid regenerants were also observed among gynogenic plants and their gynogenic origin was confirmed by SSR markers. Parents with good gynogenic potential can be utilized for introgression breeding in onion where a reduction in the breeding cycle is beneficial.